2014
DOI: 10.1128/aac.02617-13
|View full text |Cite
|
Sign up to set email alerts
|

Tranylcypromine Reduces Herpes Simplex Virus 1 Infection in Mice

Abstract: Herpes simplex virus 1 (HSV-1) infects the majority of the human population and establishes latency by maintaining viral genomes in neurons of sensory ganglia. Latent virus can undergo reactivation to cause recurrent infection. Both primary and recurrent infections can cause devastating diseases, including encephalitis and corneal blindness. Acyclovir is used to treat patients, but virus resistance to acyclovir is frequently reported. Recent in vitro findings reveal that pretreatment of cells with tranylcyprom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Reduction in viral pathology was evident in animals infected with high doses (LD 50 or LD 90 doses) and using a variety of inhibitor treatments (oral, time-release, topical, intraperitoneal). Indeed, in support of these data, Yao et al (48) reported the use of TCP to suppress HSV infection in the mouse model system. Similarly, in the rabbit eye model of herpetic keratitis, treatment of primary infection reduced the critical clinical indicators of ocular disease.…”
Section: Discussionmentioning
confidence: 82%
“…Reduction in viral pathology was evident in animals infected with high doses (LD 50 or LD 90 doses) and using a variety of inhibitor treatments (oral, time-release, topical, intraperitoneal). Indeed, in support of these data, Yao et al (48) reported the use of TCP to suppress HSV infection in the mouse model system. Similarly, in the rabbit eye model of herpetic keratitis, treatment of primary infection reduced the critical clinical indicators of ocular disease.…”
Section: Discussionmentioning
confidence: 82%
“…Naproxen was reported to be incorporated into the RNA-binding groove of the nucleoprotein of influenza A virus, suggesting its potential role in antiviral research 36 . The therapeutic potential of tranylcypromine for herpes simplex virus 1 (HSV-1) infection was evaluated because of its inhibitory activity against the histone-modifying enzyme, lysine-specific demethylase 1 37 . Raloxifene, a selective oestrogen receptor modulator, was reported to inhibit Ebola virus infection 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse brain stems were processed and stained as described in our previous reports (40,42), using Hoechst dye for DNA and antibodies against HSV-1 (Dako), HSV-1 glycoprotein C (clone 3G9; Abcam), or mouse NeuN (clone A60; Millipore).…”
Section: Methodsmentioning
confidence: 99%